The Impact of Green Marketing on the Competitiveness of Local Ecotourism-Based MSME Products - Vinandri Hapsari; Heru Subiyantoro (Greenation International Journal of Economics and Accounting, 2025)
This study analyzes the impact of green marketing on the competitiveness of MSME products based on local ecotourism in Indonesia. The ecotourism industry has experienced significant growth in response to increasing consumer environmental awareness. MSMEs implementing green marketing strategies show enhanced competitiveness through product differentiation and broader market access. The research employs quantitative methods with surveys of 150 ecotourism MSMEs in Java and Bali. Results indicate green marketing has a positive and significant effect on ecotourism MSME competitiveness, with a determination coefficient of 0.742. Green promotion and green product dimensions are dominant factors in enhancing competitive advantage. MSMEs implementing environmentally friendly practices experienced average revenue increases of 34% and market segment expansion up to 45%. Research implications highlight the importance of government support in facilitating environmentally friendly product certification and green marketing education programs for ecotourism MSME actors.